Emerging trends in modification of dietary oils and fats, and health implications- a review - Pradeep Puligundla; Prasad Shekhar Variyar; Sanghoon Ko; Vijaya Sarathi Reddy Obulam (Universiti Kebangsaan Malaysia, 2012)
In recent years, issues regading safety and wellness of dietary oils and fats have received major attention. This is particularly so in the case of structured modified fats, which are being used extensively to meet the product-specific demand primarily in bakery industry as shortenings, cocoa butter substitutes in confectionary industry, and in margarine preparation, as butter substitute. During modification stages, native oils and fats are subjected to different physical and chemical treatments such as fractionation, hydrogenation and interesterification in order to produce fats with desirable physical as well as functional properties. Numerous studies have demonstrated the adverse health effects of these modified oils and fats, especially trans fatty acids, using animal models as well as human volunteers. Consequently, the decades-old process of partial hydrogenation of oils has been abandoned in most nations. However, alternative technologies to hydrogenation are on rise, creating new trends in modified oils and fats synthesis to cater food industry needs that may have unforeseeable consequences on human health.